Sign of the Green Arrow : A Mystery Story - Snell, Roy J. (Roy Judson), 1878-1959 (Salt Lake City, UT : Project Gutenberg, 2014)
"Sign of the Green Arrow" by Roy J. Snell is a mystery novel written in the late 1930s. The story centers around a young man named Johnny Thompson, who embarks on an adventurous and potentially dangerous journey while working on a scientific expedition aboard the ship "Sea Nymph". As he navigates through mysterious surroundings, he encounters a peculiar green light signaling from a nearby island, intriguing characters including a blonde girl named Doris and her grandfather Professor Casper, and hints of espionage that elevate the tension within the narrative. The opening of the story establishes the atmosphere of suspense and adventure, beginning with Johnny's solitary shift on the deck of the ship in the tropical night. He soon spots a mysterious green arrow signal and meets Doris, who shares his curiosity about the light. Their conversation reveals hints of danger in the region involving native unrest and possible spies. As Johnny reflects on his life and the unexplained occurrences surrounding him, a sense of excitement builds around their planned explorations and the hidden secrets of the sea. The chapters that follow promise thrilling underwater discoveries, unearthing the potential threats posed by spies, all while developing Johnny's relationship with Doris and the quest for answers. (This is an automatically generated summary.)
Release date is 2014-02-02
E-text prepared by Stephen Hutcheson, Rod Crawford, Dave Morgan, and the Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Sea stories; Mystery and detective stories; Submarines (Ships) -- Juvenile fiction; Spies -- Juvenile fiction